2021
DOI: 10.1108/bfj-03-2021-0332
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of a third-party food delivery app during the COVID-19 pandemic

Abstract: PurposeThe study aims to analyze guest comments on the Uber Eats food delivery app (FDA) in the USA during the April–June 2020 COVID-19 pandemic lockdown period. Three aspects influencing customer satisfaction with the FDA were evaluated in this study: (1) performance on the app, (2) product quality and (3) service quality.Design/methodology/approachOne thousand customer comments posted on the Uber Eats Google Play app from April 1 to June 30, 2020 were analyzed in this study. The text mining technique was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
1
22
2
Order By: Relevance
“…As count or percent contribution is shown in Table 5 , overall, perceived consumer responsibility, delivery operations, social responsibility, perceived negative impact, free delivery, etc., are the most prominent dimensions related to OFD companies across emerging and developed countries. These findings differ from the previous literature ( Chen McCain et al, 2021 ; Dsouza and Sharma, 2021 ; Shah et al, 2021 ; Trivedi and Singh, 2021 ) that observed food quality and safety measures, socialization, and marketing are the main themes for OFD companies during COVID-19. Our topics seem more enlightening and COVID-19 pandemic-oriented rather than topics related to the usual expectations from OFD companies.…”
Section: Discussion and Managerial Implicationscontrasting
confidence: 99%
See 4 more Smart Citations
“…As count or percent contribution is shown in Table 5 , overall, perceived consumer responsibility, delivery operations, social responsibility, perceived negative impact, free delivery, etc., are the most prominent dimensions related to OFD companies across emerging and developed countries. These findings differ from the previous literature ( Chen McCain et al, 2021 ; Dsouza and Sharma, 2021 ; Shah et al, 2021 ; Trivedi and Singh, 2021 ) that observed food quality and safety measures, socialization, and marketing are the main themes for OFD companies during COVID-19. Our topics seem more enlightening and COVID-19 pandemic-oriented rather than topics related to the usual expectations from OFD companies.…”
Section: Discussion and Managerial Implicationscontrasting
confidence: 99%
“…Exceptions to this are financial impact and consumers' perceived behaviors of Zomato; delivery operations of Swiggy; promocode and food delivery of Uber Eats. These findings are different from the findings of Chen McCain et al (2021) in the sense that they found that negative sentiment is more than positive sentiment.…”
Section: Discussion and Managerial Implicationscontrasting
confidence: 99%
See 3 more Smart Citations